Crystal Structure of the Autochaperone Region from the Shigella flexneri Autotransporter IcsA - Kühnel, Karin (American Society for Microbiology, 2011)
The IcsA (intracellular spread gene A) autotransporter from Shigella flexneri is a key virulence factor. We identified a stable fragment comprising residues 591 to 758, which corresponds to the autochaperone region of the IcsA passenger domain. We showed that thermal unfolding of the autochaperone region is reversible and determined its crystal structure at 2.0-Å resolution.